DIALEKTIKA KRISIS TOLERANSI DI INDONESIA TAHUN 2017 (TELAAH ACARA INDONESIA LAWYERS CLUB TENTANG FENOMENA LGBT) - Nurul Avifah; Sholikhatun Hanifia (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
Discussions about LGBT (Lesbian, Gay, Bisexual, and Transgender) in Indonesia do not seem to only begin to be serious but also look to crush tolerance. Seriously because various media often take up the theme, even Indonesia Lawyers Club (ILC), one of the favorite talkshow programs in the country, to discuss it several times. Interestingly, those who voiced tolerance, both pro and contra, were even more arrogant and forgot the essence of tolerance itself. This is where tolerance appears to be being tested and questioned. The purpose of this paper is to examine the dialectic of the crisis of tolerance in Indonesia in 2017 by clarifying the interpretation of the Qur'an that discusses LGBT. While this writing method is descriptive analytical using media analysis, which focuses on 2017 ILC shows, especially those related to LGBT. The results of this study provide a solution that reminds the Indonesian people, that tolerance exists because differences (not similarities) and the resolution of LGBT problems must be based on the values, philosophy and principles of the Republic of Indonesia and the noble goal of being a faithful and devoted human being to the One God, not an interest personal. This research is expected to improve the perspective of the Indonesian people towards tolerance related to LGBT. So that the relevance to the study of crisis tolerance in Indonesia in 2017 is very strong and needs to be prioritized.